NEED ASSESSMENT OF ASSISTIVE TECHNOLOGY IN CHILDREN WITH MULTIPLE DISABILITIES - Safdar, Dr. Saba; Khan, Dr. Shahzad Ali; Azam, Dr. Naila; Mahmood, Dr. Humaira; Pervaiz, Dr. Farrah (Pakistan Armed Forces Medical Journal, 2019)
Objective: To quantify the need for assistive technology in children with disabilities and determine the barriers for the use of assistive technology and formulate recommendations for the optimum use of assistive technology for children with disabilities. Study Design: A descriptive cross sectional study design. Place and Duration of Study: Study was carried out in National Institute of Rehabilitation Medicine, Islamabad from Apr 2018 to Sep 2018. Material and Methods: A WHO structured questionnaire was used. It assessed the assistive technology needs in children with disabilities. Due to complexity of the questionnaire, it was explained to the respondents of thestudy. Sampling was done through non-probability convenient sampling. One hundred and thirty eight respondents were included in the study. SPSS was used for Statistical analysis of the data. Results: Overall, the needs of children were highest for the mobility aids. Among which mostly need Lower limb orthosis (43.5%) and walking frame (37%). Various barriers were identified in access to assistive technology but the most common was lack of awareness (34.8%). It also showed highly significant association of age with walking, communication, remembering and performing day to day activities (p=0.000) and significant association of age with barriers (p=0.014) and health condition (p=0.001) and between employment status and barrier (p=0.002), while no association was seen among other variables. Conclusion: To improve the health status of poor children living with disabilities, assessment of their basic needs for assistive technology is crucial so that they can be given equal rights as children without disabilities and the barriers which they are facing in the access to health care could be eliminated.